ISOLATION AND MOLECULAR CHARACTERIZATION OF PLASTIC DEGRADING BACTERIA FROM DUMPED GARBAGE SOIL - SD, SHRUTHI; GHOSH, SAMBUDDHA; M, MEGHANACHOWDARY; MEGALA S, MANI (Innovare Journal of Life Sciences, 2020)
Objective: Plastics are polymers that are widely in application in our day-to-day life. The plastic wastes accumulation is causing threat to the environment as it causes environmental pollution and creates imbalance in the ecosystem. The natural degradation of plastic is too time consuming and the ways to do it are not highly successful. An eco-friendly approach to plastic degradation is using microbial degradation method. Microorganisms play an important role in biological decomposition of various materials in our environment. Thus, the main objective of the present study is isolation and molecular characterization of plastic degrading bacteria from dumped garbage soil. Methods: The samples were collected from two different locations in Bengaluru and further subcultured to obtain pure culture. Gram’s staining was performed to identify bacterial strains and few tests were conducted to find out the biochemical properties of the bacteria. Molecular characterization of isolated bacteria was performed using 16S rRNA method, BLAST and phylogenetic tree were constructed. Results: The bacterial isolates were found to be, namely, Aeromonas caviae, Aeromonas hydrophila, Salmonella enterica, and Pseudomonas aeruginosa. The polythene bag biodegradation was analyzed by incubation for a period of 2 months in liquid culture method. Conclusion: The results of the study ensure that A. hydrophila showed more degrading capability which is followed by A. caviae, whereas Pseudomonas aeruginosa and S. enterica did not contribute in much of the plastic degradation. The weight loss of polythene bag is maximum with higher incubation period rate. From the observation, we conclude that bacteria have more capability to cleave polymer.